Main Trends in the Soviet Reform of Criminal Law - Grzybowski, Kazimierz (1960)
Many organizations have legacy applications and strive to modernise them in order to react on changes and adapt to the new environment, the cloud. The enticements are quite a few but the risks are lurking as well. How to migrate a legacy application to the cloud is an unanswered question for many organizations. We look at how research has answered this question and the methods and tools they provide. The research partially answers the question of migration of legacy application to the cloud. The methods and tools are still quite granular, not that automated and is very dependent of what type of legacy application and the aim of the end result is